Impact of Energy consumption and Economic policy uncertainty on Ecological footprint: Evidence from BRICS countries - Arek-Bawa, Oghenefejiro (University of the Witwatersrand, Johannesburg, 2024)
In the past years, a growing concern has been directed towards global environmental quality and the energy required to sustain economic growth. A crucial element in current literature is the influence of economic policy uncertainty (EPU) and on Ecological Footprint (EFP). Given the significant global influence of the BRICS (Brazil, Russia, India, China, and South Africa) group, examining it through their lens will benefit the international context. Therefore, this study utilized AMG and CCEMG methodologies to investigate the impact of energy consumption (EC) and EPU on the EFP in BRICS countries. This study enriches the current literature further by disaggregating EC into REC (Renewable Energy Consumption) and NREC (Non-renewable Energy Consumption) and subsequently looking at the consequences of individual renewable energy sources on the EFP. The study presents empirical findings that show panel and country-specific results and demonstrate that EC and NREC increase EFPs. In contrast, only China's REC positively impacted the environment. EPU has significantly negatively affected the EFP when considering individual REC. This study recommends policymakers accelerate the transition to a sustainable future by considerably increasing support for additional investments and subsidies to the widespread adoption of renewable energy as a primary source to diminish environmental decay
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce (Economics/Economic Science) in the School of Economics and Finance, University of the Witwatersrand, Johannesburg 2025
Keywords: SDG-8: Decent work and economic growth